Changes of soil and understory biomass before and after the harvesting of Eucalyptus camaldulensis plantation in Thong Pha Phum, Kanchanaburi, Thailand - Kobayashi S.; Yarwudhi, C.; Suksawang S. (1997)
Environmental changes must be initiated by forest harvesting. The harvesting of timber has affected forest ecosystems in various ways which includes degradation, shortage of forest water supply, soil loss and green house gas emission. Selective cutting, clear-cut, fire and burning are major causes of land degradation, though forest harvesting becomes a trigger to other forms of land utilization. However, while forest harvesting affects changes in ecosystem, land utilization afterwards may cause severer impacts on natural ecosystems. Nevertheless, the affects of forest harvesting have not fully been understood. Information on the long term impact of tree harvesting on forest ecosystems especially with regard to changes in vegetation, soil and productivity, is lacking. The harvesting impacts to ecosystems vary with time and method of logging, timber transporting method, logged tree species, soil characteristic, topography, local rain fall pattern and others. Therefore, impacts are assessed in relation to logging and timber transportation measures by taking many experimental plots in various conditions by a long term monitoring. Forest harvesting impacts on ecosystem were surveyed within a Eucalyptus camaldulensis plantation in Thong Pha Phum, Kanchanaburi to determine a sustainable rotation for the plantation. The experimental site had alraedy received severe damege to the soils during the first forest harvesting which was done to convert the natural forest to an Eucalyptus plantation. After the harvesting of Eucalyptus, soil and understory biomass were slightly changed, the thickness of A0 & A horizons, the hardness of A & B horizons and contents of Cations decreased, whereas bulk density and the saturated hydraulic conductivity rates increased. Severe variations in cha nges of soil properties was obeserved at yarding road, this was caused by the compaction of the topsoil by a yarding car. On the other hand, topsoil physical properties were improved by skidding when compared with the resuts of three different study sites